2018
DOI: 10.1038/s41392-018-0015-8
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptional cofactors Ski and SnoN are major regulators of the TGF-β/Smad signaling pathway in health and disease

Abstract: The transforming growth factor-β (TGF-β) family plays major pleiotropic roles by regulating many physiological processes in development and tissue homeostasis. The TGF-β signaling pathway outcome relies on the control of the spatial and temporal expression of >500 genes, which depend on the functions of the Smad protein along with those of diverse modulators of this signaling pathway, such as transcriptional factors and cofactors. Ski (Sloan-Kettering Institute) and SnoN (Ski novel) are Smad-interacting protei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
70
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 94 publications
(77 citation statements)
references
References 283 publications
(330 reference statements)
2
70
0
Order By: Relevance
“…While Ski effectively sequesters and binds Smads, which are needed for the canonical response to TGF‐ β 1 , the mechanisms by which Ski modulates these functions may extend beyond its role as an endogenous repressor of TGF‐ β 1 (Tecalco‐Cruz et al. ). We have shown that TGF‐ β 1 itself leads to activation and movement of Ski to the nucleus (bound to R‐Smads) in MFB (Cunnington et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…While Ski effectively sequesters and binds Smads, which are needed for the canonical response to TGF‐ β 1 , the mechanisms by which Ski modulates these functions may extend beyond its role as an endogenous repressor of TGF‐ β 1 (Tecalco‐Cruz et al. ). We have shown that TGF‐ β 1 itself leads to activation and movement of Ski to the nucleus (bound to R‐Smads) in MFB (Cunnington et al., ).…”
Section: Discussionmentioning
confidence: 99%
“…To effect this specific response in combination with decreased MFB marker proteins and adhesion proteins ( FAK and paxillin) Ski may serve as a scaffold for number of cofactors including Smads (Tecalco‐Cruz et al. ). On the other hand, in chronic cardiac injury (infarcted hearts) we have found that the intracellular distribution of Ski is shifted to the cytosol (Cunnington et al.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations